The discrepancy between the values of the Hubble constant and the effect of dark energy on baryonic matter - Harutyunian, H. A.
It seems clear that researchers have not yet fully appreciated the true implications of the discovery of dark energy for understanding evolutionary processes in the baryonic universe. Based on general physical considerations, we consider here the influence of dark energy on baryon objects at the level of atomic nuclei and elementary particles. For such an analysis, the concept is adopted, according to which the entire baryonic Universe interacts with dark energy on all cosmic scales. The consequences seem quite dramatic, since the accumulation of energy in the baryon world changes the energy balance and reduces the binding energy of all objects, including atomic nuclei. Consequently, the nuclear mass defect decreases, their mass increases, and both effects make the nuclei more and more unstable. This leads to the destabilization of all nuclei and their gradual transfer to the stage of radioactive decay, which increases over time the relative amount of light elements, including hydrogen. Evolution under the influence of dark energy, on the other hand, increases the masses of atomic nuclei. We have used this hypothetical effect to interpret the so-called ”Hubble tension” paradox. This also makes it possible to estimate the growth of the proton mass due to dark energy.
Keywords: Astronomy